EFEK ISOFLAVON FITOESTROGEN DARI EKSTRAK Pueraria lobata TERHADAP MEMORI DAN AKTIVITAS KOLINERGIK DI HIPPOKAMPUS CA1 PADA TIKUS HIPOESTROGEN - Safithri, Fathiyah; Ali, Mulyohadi (Universitas Muhammadiyah Malang, 2010)
Data from retrospective and case-conttrole showed that estrogen replacement therapy (ERT) could prevent ang delayed againstAlzheimer Disease (AD). The using of ERT is still controversial because of their long-term side effect. Isoflavon as a part of phytoestrogenhas potential effect as an alternative substitute for ERT. The aim of this study is to examine the effect of phytoestrogen from Pueraria lobataextract in increasing memory’s function and whether it occur by the increased of cholinergic activity in CA1 hippocampus. Exploration studyperformed by three step. First, determined genistein and daidzein concentration in Pueraria lobata extract, as basic of dose determining.Second, oophorectomy performed to made a hypoestrogenic rat’s model; and third, determined method memory’s function in rats. This studyused twenty five female Rattus novergicus strain Wistar, 10 -11 weeks of age, five rats were normal rats (N) as first group and twenty ratswere hypoestrogenic rats for 2nd, 3rd, 4th, and 5th groups. All of the hypoestrogenic rat were devided into 4 groups, each 5 rats. Hypoestrogenicrats group without Isoflavon Genistein Daidzein supplement (OVX), hypoestrogenic rats group with Isoflavon Genistein Daidzeinsupplement (OVX+IGD) dosage of 15, 30, and 60 mg/kgweight/day each. The IGD was given for 21 days. The Morris Water Morris(MWM) test was performed in 17th, 18th, 19th, 20th, and 21st day. On 22nd day rats were killed. Frozen section of the brain was performedimmediately. Cholinergic activities on CA1 hippocampus were examined with AChE staining. A significant difference was found onmemory’s function and cholinergic activities on CA1 hippocampus between OVX and OVX+IGD groups at all doses (p value = 0,000 ofeach). No significant difference on IGD effect toward brain weight (p=0,936) and pyramidal cell number on CA1 hippocampus (p=0,961).It was suggest that increased memory’s function on OVX+IGD groups were caused by the increased of cholinergic activities on CA1hippocampus.Key word : Isoflavones; phytoestrogen; Genistein; Daidzein; Pueraria lobata; Memory; cholinergic.